STUDY THE EFFECT OF DRAWBAR AND FIELD EFFICIENCY USING OF ACOMBINE IMPLEMENT USED IN THE INSTALLATION OF SUBSURFACE IRRIGATION PIPES AND DRIP IRRIGATION UNDER DIFFERENT DISCHARGE - & Al-kaabi, Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
An experiment was conducted in the field of the University of Baghdad in 2015 In loamy sand soil to study the effect drawbar and field efficiency using of a combine implement used for installation subsurface irrigation pipes and drip irrigation under different discharges. Subsurface irrigation system and drip irrigation system with three levels of discharge included 2.5,3.0 and3.5 L-1 were used in this experiment. Field efficiency, drawbar, soil moisture content and soil bulk density were measured in this stdy. Nasted design under randomized complete block design(CRBD) with three replications were used in this experiment. Least significant differences (L.S.D) at 0.05 levels were used to compare the mean of treatments. The results were showed the follows: Subsurface irrigation got 12.7 kw drawbar and 29.45% moisture content and 1.43g/cm3 bulk density g/cm3 and 84% field efficiency.While Drip irrigation system got 9.73kw drawbar and 25.19% moisture content and 1.47g/cm3 bulk density and 89% field efficiency. The successful of using combine implement to install subsurface irrigation pipes with tillage at the same time.